(untitled) (Faridpur Medical College Journal, 2016)
Stroke is one of the most common medical emergency. A total number of 100 randomly selected clinically and CT proven acute stroke patients were studied at medicine and neurology ward of Faridpur Medical College Hospital (FMCH), Faridpur from January to July, 2014 with a view to study the clinical features and risk factors of Stroke. Among 100 patients, stroke was found most commonly in 59-70 years age group. Ischaemic stroke was 56%, haemorrhagic stroke was 39% and haemorrhagic infarct was 5%. Most of the patients were male with male-female ratio was 1.6:1. The commonest risk factor was hypertension found in 60%, diabetes mellitus found in 17%, smoking was present in 54% patients and dyslipidaemia was present in 22% cases. History of heart disease (Myocardial infarction was present in 2% patients, valvular heart disease was present in 4% patients) was present in 6% patients. The commonest presentation in both ischaemic and haemorrhagic stroke was hemiplegia (61%). Headache (14%) and vomiting (10%) were found to be more common accompaniment in haemorrhagic stroke. Loss of consciousness was present in 34% patients. Alcohol intake was not found in any patient. Faridpur Med. Coll. J. Jan 2016;11(1): 23-25